Molecular epidemiology of Japanese avian Pasteurella multocida strains by the single-enzyme amplified fragment length polymorphism and pulsed-field gel electrophoresis - Nattawooti Sthitmatee (2018)
Molecular epidemiology analyses of the 36 clinical isolates of Pasteurella multocida from various avian hosts in Japan between 1976 to 2007 including 5 reference strains from the U.S.A., Taiwan and Indonesia were performed by employing the single-enzyme amplified fragment length polymorphism (SE-AFLP) comparison with the classical ApaI-based pulsed-field gel electrophoresis (PFGE). As the results, SE-AFLP gave 21 profiles while PFGE gave 20 profiles. The Simpson's index of diversity analysis indicated that SE-AFLP gave a high discrimination power than PFGE. This concluded that SE-AFLP is a higher discrimination power than PFGE to differentiate avian P. multocida isolates in Japan. In addition, the genetical profiles suggested that there is the evolution of somatic serotype 3 strain in the indigenous host of Japan.